Dynamic Total-Body PET/CT Imaging Reveals Kinetic Distribution of 68Ga-DOTATATE in Normal Organs. (18th January 2023) - Yin, Hongyan; Liu, Guobing; Hu, Yan; Xiao, Jie; Mao, Wujian; Lv, Jing; Yu, Haojun; Lin, Qingyu; Cheng, Dengfeng; Shi, Hongcheng
Abstract : Objective . To investigate the biodistribution and kinetic constants of 68 Ga-DOTATATE in normal organs through dynamic total-body positron emission tomography/computed tomography (PET/CT). Methods . Seven patients who experienced endoscopic resection of gastric neuroendocrine tumor were enrolled. Dynamic total-body PET/CT scans over 60 min were performed. Time-activity curves were obtained by drawing regions of interest in normal organs. Rate constants, including K 1, k 2, k 3, and vB, were computed using a two-tissue compartment model. Factor analysis was used to compare the rate constants among subjects and regions. Hierarchical cluster analysis was performed to identify organs with similar kinetic characteristics. Results . The highest uptake of 68 Ga-DOTATATE was observed in the spleen followed by kidneys, adrenals, liver, pituitary gland, pancreas head, prostate, pancreas body, and thyroid, parotid, and submandibular glands. Low background level of 68 Ga-DOTATATE uptake was observed in the nasal mucosa, bone, blood pool, and cerebrum. In addition, the uptake in the pancreas head was noted to be higher than the pancreas body (P < 0.001 ) on the basis of each time point of dynamic PET. There were differences of rate constants among different organs. The mean K 1 ranged from 0.0507 min −1 in the left nasal mucosa to 1.21 min −1 in the left kidney, and mean k 2 ranged from 0.0174 min −1 in the spleen to 4.4487 min −1 in the left cerebrum. The mean k 3 ranged from 0.0563 min −1 in the right cerebrum to 4.6309 min −1 in the left adrenal, and mean vB ranged from 0.0001 in the left cerebrum to 0.2489 in the right adrenal. However, none of the rate constants was significantly different among subjects or among different sites within a single organ. Three groups of organs with similar kinetic characteristics were identified: (1) cerebrum; (2) pituitary gland, liver, adrenal, and prostate; and (3) nasal mucosa, parotid and submandibular glands, thyroid, spleen, pancreas, kidney, and bone. Conclusion . Uptake and clearance of 68 Ga-DOTATATE, in terms of kinetic constants, were different in different organs. The kinetic parameters of 68 Ga-DOTATATE in different organs provide a reference for future dynamic PET imaging.